In-Session Reflective Functioning: Relationship With the Presence and Depth of Work on Conflict or Personality Functioning - de la Cerda, Cecilia; Dagnino, Paula (Frontiers in Psychology, 2021)
Mentalizing, conceived as the capacity to attribute intentional mental states as implicit or underlying one’s behavior or others, has gained interest within psychodynamic clinical research for its potential as a change mechanism. Variations and qualities of mentalization have been studied through Reflective Functioning (RF). But few are the studies analyzing it throughout the psychotherapeutic interaction, identifying its level for therapists and patients. On the other hand, brief psychodynamic therapy has a long tradition for establishing a focus to be worked upon. Lately, a multischematic focus has arisen, considering conflict and personality functioning focus as key elements on successful psychotherapies. This study aimed to identify mentalizing manifestations of patients and therapists through change episodes of one successful brief psychodynamic therapy and establish the relationship between these mentalizing manifestations and the type and depth of therapeutic focus being worked on (conflict or personality functioning). Results: Patient concentrated 91% of low or failure on Reflective Functioning (RF); meanwhile, the therapist only had 9%. As for moderate to high RF, patients had 39% meanwhile therapists had 61%. The patient showed a similar number of low or failure RF interventions and moderate to high RF interventions in conflict episodes. Meanwhile, the therapist only performs medium to high-level RF interventions. In episodes in which personality functioning is worked, both patient and therapist show a greater presence of interventions of moderate to high levels of RF. Finally, mentalizing interactions during conflict focus, moderate to high RF from the therapists relate with failures of the patient. In contrast, therapists` similar levels of RF relate to an increased RF level from the patient. During personality functioning focus, no failures were found on RF of the patient even when the therapist makes a low or failure RF or a moderate to high RF intervention. Discussion: The prevalence of turns of speech with moderate to high RF may be related to the fact that the segments analyzed are episodes of change. Mentalizing and non-mentalizing interactions found only on conflict episodes may relate to the psychoanalytic approach, conflict as a central element of treatment, which could higher reflective level of the therapist.